Burnout and pre-competition: A study of its occurrence in brazilian soccer players - Verardi, Carlos Eduardo Lopes [UNESP]; Nagamine, Kazuo Kawano; Domingos, Neide Aparecida Micelli; De Marco, Ademir; De Oliveira Santos Miyazaki, Maria Cristina (My University, 2015)
The objective of this study was to identify and interpret the occurrence of those symptoms associated with the burnout syndrome during the pre-competition phase.A total of 134 male soccer players participated in the study, 71 professionals (Mage = 22.77 ± 3.98 years) and 63 amateurs (Mage = 17.18 ± 0.84 years) from three teams participating in the São Paulo State Championship, Series A-1 and A-2 (professional category) and the São Paulo Junior Soccer Cup (amateur category), organized by the São Paulo Soccer Federation, State of São Paulo, Brazil. In order to evaluate the Burnout Syndrome, a version of the Athlete Burnout Questionnaire (ABQ) was used, an instrument developed especially for the evaluation of burnout in athletes. Values associated with greater vulnerability and, consequently, greater risk of evolving to the syndrome, were observed in a small portion of those players interviewed. The impact represented by the players with higher scores for burnout and the importance of such in relation to the team should be investigated.
Keywords: Amateurs; Burnout; Professionals; Soccer